Plasma Levels of Cyclic Nucleotides in Patients with Essential Hypertension - TSUCHIYA, Seiya; OGAWA, Kouichi; SATAKE, Tatsuo (Japanese Heart Journal, 1980)
We studied plasma levels of cyclic nucleotides and their responses to submaximal exercise as an endogenous adrenergic stimulation in normal subjects, untreated and treated patients with essential hypertension to assess the roles of various hormones and the autonomic nervous system in essential hypertension. Plasma c-AMP level was significantly higher in untreated, diuretic-treated patients and those treated with propranolol than in normal subjects, but plasma c-GMP level was comparable in normal subjects and untreated patients. Plasma c-AMP decreased significantly, whereas plasma c-GMP increased significantly, after chronic propranolol therapy. Plasma c-AMP increased significantly after submaximal exercise in normal subjects, untreated patients and those treated with propranolol, but plasma c-GMP increased significantly only in normal subjects. The increase in plasma c-AMP was significantly higher in untreated patients than in normal subjects and patients treated with propranolol. Moreover, the percent increase in plasma c-AMP was significantly higher in untreated patients than in those treated with propranolol. Therefore, it is suggested that the sympathetic nervous system may be hyperactive, and that a hyperreactivity of the β-adrenergic receptors may play an important role in essential hypertension.